Ensaios em federalismo fiscal: efeitos da descentralização do imposto territorial rural e evidências de clientelismo - Caldeira, Thiago Costa Monteiro (2021)
This paper evaluates the effects of the decentralization of the tax on rural real state property (ITR) from the Union to the municipalities in Brazil, allowed by constitutional amendment in 2003, and evaluates the hypothesis of clientelistic practices by mayors linked to rural activities. The purpose of the amendment was to increase the enforcement of the ITR law, given the history of tax evasion and low collection effort by the federal government. Based on collection data between 2002 and 2017 and decentralizations in more than two thousand Brazilian municipalities, I estimated a model of difference in differences with multiple treatment periods. The results indicate that there is an average positive effect between 37.63% and 62.08% in the ITR collection resulting from decentralization to the municipalities, in relation to continuing centralized management with the Union. The effect is increasing over the years exposure to treatment, indicating that municipalities are learning over time to charge and monitor, and the result is robust for placebo tests and samples by geographic region and municipality size. To assess the clientelist hypothesis, I adopted a discontinuous regression with close elections as a discontinuity variable. The results indicate that ruralist mayors avoid assuming the management of the ITR, but that, in doing so, they behave in a similar way to non-ruralist mayors in terms of the intensity of the collection and inspection effort. The result differs for the Northeast region, where it was identified that being the municipality managed by a ruralist mayor reduces the ITR collection between 12.15% and 28.82%, confirming previous studies that indicate a greater existence of clientelistic practices in this region. It is concluded that, in terms of collection and inspection efforts, the tax has been better managed at the municipal level and that there is still potential for an increase in collection.